2018
DOI: 10.1111/ijd.13874
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin treatment for folliculitis decalvans: a retrospective case‐series study

Abstract: Contrary to general belief, oral isotretinoin monotherapy resulted in complete response in the majority of patients in this study. Based on this finding, we think oral isotretinoin ≥0.4 mg/kg/day should be given for ≥3 months to minimize the likelihood of relapse. In addition, we think oral isotretinoin monotherapy should be considered a promising treatment alternative for FD that warrants further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
0
16
0
4
Order By: Relevance
“…The highest level of evidence was grade 3, encompassing 7 studies with 263 patients (Table I). [3][4][5][6][7][8] A multicenter, retrospective study showed that 15 patients treated with a 10-week course of clindamycin and rifampicin achieved the longest disease remission at an average of 7.2 months. The remission period was shorter among those treated with doxycycline or azithromycin for 3-6 months, who subsequently received adjunct topical antibiotics and intralesional corticosteroids.…”
Section: Updates In Therapeutics For Folliculitis Decalvans: a Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest level of evidence was grade 3, encompassing 7 studies with 263 patients (Table I). [3][4][5][6][7][8] A multicenter, retrospective study showed that 15 patients treated with a 10-week course of clindamycin and rifampicin achieved the longest disease remission at an average of 7.2 months. The remission period was shorter among those treated with doxycycline or azithromycin for 3-6 months, who subsequently received adjunct topical antibiotics and intralesional corticosteroids.…”
Section: Updates In Therapeutics For Folliculitis Decalvans: a Systemmentioning
confidence: 99%
“…Of note, treatment of FD with isotretinoin was associated with hyperlipidemia (14/39) in another retrospective review. 8 Newer therapeutic options have been described in case reports and case series in recent years, and accordingly, the level of evidence is very low ( grade 4) (Table II). 1 Red light photodynamic therapy resulted in clinical improvement in 9 of 10 patients, with 6 patients exhibiting disease remission.…”
Section: Updates In Therapeutics For Folliculitis Decalvans: a Systemmentioning
confidence: 99%
“…There is, however, increasing evidence supporting oral isotretinoin as a first-line treatment for severe forms of FD. 2,3 In a series of 49 men with FD who were treated with isotretinoin, Aksoy et al 2 reported complete and partial response rates of 82% and 10%, respectively. The optimal treatment regimen was yet to be determined, and patients who received oral isotretinoin ($0.4 mg/kg/day) for at least 3 months had the best response, with two-thirds of these patients never experiencing a relapse.…”
mentioning
confidence: 99%
“…The efficacy of isotretinoin could be explained by its direct inhibitory effect on the immune system. 2,3 It inhibits the migration of neutrophils into the skin and modulates the innate immune system defenses against Gram-positive bacteria through decreasing the Toll-like receptor 2 level. 2,3…”
mentioning
confidence: 99%
See 1 more Smart Citation